Family History, Tobacco Smoking, and Risk of Ischemic Stroke - Fan, Mengyu (J Stroke, 2019)
BACKGROUND AND PURPOSE: Both genetic factors and smoking are associated with ischemic stroke (IS) risk. However, little is known about the potential interaction of these factors. We aimed to assess whether smoking and a positive family history interact to increase the risk of IS. METHODS: The nationwide prospective study recruited 210,000 men and 300,000 women in 2004 to 2008 at ages 30 to 79 years. During 9.7 years of follow-up, we documented 16,923 and 20,656 incident IS cases in men and women without major chronic diseases at baseline, respectively. Multivariable Cox regression models were used to examine associations between family history and IS. Likelihood ratio tests were used to test the smoking-family history interactions on IS. RESULTS: About 67.8% (n=135,168) of men ever smoked regularly compared with 2.7% (n=7,775) of women. Among men, a significant interaction between family history and smoking on IS was observed (P for interaction=0.03), with more pronounced association between family history and IS among ever-regular smokers (hazard ratio [HR], 1.21; 95% confidence interval [CI], 1.16 to 1.27) than among never-smokers (HR, 1.11; 95% CI, 1.01 to 1.23). The association between family history and IS among ex-smokers after more than 10 years of cessation (HR, 1.01; 95% CI, 0.85 to 1.20) appeared similar to that among never-smokers. Among women, a similar but not significant interaction between family history and smoking on IS was observed. Ever-regular smokers who had a family history of stroke had the highest risk of IS. CONCLUSIONS: Among Chinese men, the association of family history with IS was accentuated by smoking, and such accentuation tended to be lowered by cessation.